Hybrid 2D Dual‐Metal–Organic Frameworks for Enhanced Water Oxidation Catalysis. (30th April 2018) - Rui, Kun; Zhao, Guoqiang; Chen, Yaping; Lin, Yue; Zhou, Qian; Chen, Jiayi; Zhu, Jixin; Sun, Wenping; Huang, Wei; Dou, Shi Xue
Abstract: Metal–organic frameworks (MOFs) and MOF‐derived nanostructures are recently emerging as promising catalysts for electrocatalysis applications. Herein, 2D MOFs nanosheets decorated with Fe‐MOF nanoparticles are synthesized and evaluated as the catalysts for water oxidation catalysis in alkaline medium. A dramatic enhancement of the catalytic activity is demonstrated by introduction of electrochemically inert Fe‐MOF nanoparticles onto active 2D MOFs nanosheets. In the case of active Ni‐MOF nanosheets (Ni‐MOF@Fe‐MOF), the overpotential is 265 mV to reach a current density of 10 mA cm −2 in 1m KOH, which is lowered by ≈100 mV after hybridization due to the 2D nanosheet morphology and the synergistic effect between Ni active centers and Fe species. Similar performance improvement is also successfully demonstrated in the active NiCo‐MOF nanosheets. More importantly, the real catalytic active species in the hybrid Ni‐MOF@Fe‐MOF catalyst are unraveled. It is found that, NiO nanograins (≈5 nm) are formed in situ during oxygen evolution reaction (OER) process and act as OER active centers as well as building blocks of the porous nanosheet catalysts. These findings provide new insights into understanding MOF‐based catalysts for water oxidation catalysis, and also shed light on designing highly efficient MOF‐derived nanostructures for electrocatalysis. Abstract : A highly efficient 2D metal–organic frameworks (MOF)‐based hybrid electrocatalyst for the oxygen evolution reaction (OER) is demonstrated by in situ deposition of electrochemically inert Fe‐MOF nanoparticles onto the active Ni‐MOF nanosheets. This work provides new insights into understanding MOF‐based catalysts for water oxidation catalysis, and sheds light on developing MOF‐derived nanostructures for electrocatalysis.